One class of the equations of infinite order in generalized derivatives - Korobeinik, J. F. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Ю. Ф. Коробейник. Об одном классе уравнений бесконечного порядка в обобщенных производныхJ. F. Korobeinikas. Begalinės eilės diferencialinių lygčių su apibendrintomis išvestinėmis klausimu